OPPORTUNITIES FOR INCREASING THE EXPORT OF LATVIA TO UE COUNTRIES - Pancenko, Erika; Ivanova, Tatyana (Copernican Journal of Finance & Accounting, 2021)
The relevance of this study is tied to the fact, that more effective application of export potential represents a major step towards the integration of Latvia’s economy into a unified economic framework with other European Union countries. In addition, the lack of a generally accepted methodology for assessing export potential increases the significance of these studies from a methodological point of view. The purpose of this study is to analyse the trends in Latvian exports and assess the possibilities of increasing the volume of exports of goods to the EU countries. This study applied quantitative and qualitative methods of analysis, analysis of statistical data, methods for assessing the intensity, complementarity of trade between two countries and the potential for exporting Latvian goods to EU countries. The study identifies the countries and categories of goods where Latvian trade potential to EU can be increased. The authors of the article propose criteria for determining possibility of increasing the export of various groups of goods. The paper may be of interest to all export transaction participants, including manufacturers, merchants, and professional associations. The export expansion assessment method applied by the authors may be adopted by exporting companies to identify groups of goods that have export growth reserves.